Monsters, Inc. (Parrogon Books Ltd, 2014)
Sulley is the top Scarer at Monsters, Incorporated- a company that collects children's screams to power the city of Monstropolis. One night, after a little girl wanders into the monster world, there's a race to return her.
Keywords: Juvenile Fiction